Double-stranded block copolymer with dual-polarized linker for improving dielectric and electrical energy storage performance. (3rd October 2017) - Chen, Jie; Long, Cheng; Li, Hongfei; Han, Huijing; Sun, Ruyi; Xie, Meiran
Abstract: The double-stranded block copolymers containing ionic conductive and strong polar segments were synthesized by ring-opening metathesis polymerization, and self-assembled into the hollow sphere nanostructure. These block copolymers displayed high dielectric constant of 25, low dielectric loss of 0.02, enhanced stored/released energy density of 2.60/2.38 J cm −3 at 245 MV m −1, and good charge-discharge efficiency of 91.5%, which were much better than those of double-stranded block copolymers without the strong polar substituents on the aromatic linker. The excellent dielectric properties of copolymers were attributed to the combination of strong dipolar, ionic, and interfacial polarizations, as well as the well-defined nanostructure to effectively inhibit the leakage current of the conductive domains by the insulating blocks. Graphical abstract: Highlights: The double-stranded ionic block copolymers are synthesized and self-assembled into the hollow sphere nanostructure. The block copolymers display high dielectric constant, low dielectric loss, and enhanced energy density. The excellent dielectric properties of copolymers are attributed to the multiple polarizations and regular nanostructure.